THE ESSENTIALITY OF EARLY URBANISM IN UNDERSTANDING AFRICAN PREHISTORY: A FOCUS ON WEST AFRICA - (:unkn) unknown (My University, 2022)
This article has focused on the Essentiality of Early Urbanism in Understanding African Prehistory, with a bias on West Africa. It examines the meaning and imperative of urbanization in prehistory and also looks at the various sources for the study of early urbanization, as well as interrogates the diverse research views on the application of Western meanings of urbanization in the study of ancient urban centres in African societies. Data for this research has been elicited via secondary sources or written documents. This paper therefore contributes to what is so far known about the subject of urbanization in prehistoric studies, particularly in the context of African prehistory. However, the quantum of research on urbanization in Africa, (especially in West Africa) is so far insignificant to have a generalized position on what constitutes the entire features of the ancient urban centres in the West African Region. Hence, there is a scholarly need for more research to pave the way for greater understanding of what constitutes the major features of early urban centres in the region.
Keywords: African Research